The research of railway freight statistics system and statistical methods - Wu Hua-Wen; Wang Fu-Zhang (Institute of Advanced Engineering and Science, 2013)
EXT is a JavaScript framework for developing Web interfaces, this paper describes the Ext framework and its application in railway freight statistical and analyzing system and Statistical methods. the paper also analyzes the design, function, implementation and so on of the system in detail. As information technology and the requirements of railway transportation organization and operation continue to improve, railway freight statistical and analyzing system improves obviously in the index system, decision analysis and other aspects, better meeting the work requirements. It will play a more important role in the railway transport organization, management, passenger and freight marketing. DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2206